Clinico-Radiological Assessment as A Predictor of Difficult Laparoscopic Cholecystectomy - Timilsina, Bishow Deep; Timilsina, Babita Subedi (Journal of National Heart and Lung Society Nepal, 2024)
Background: Laparoscopic cholecystectomy (LC) is the standard treatment for gallstone disease, but predicting difficult cases and conversion to open surgery remains challenging. This study aimed to identify preoperative clinic-radiological factors associated with difficult LC and conversion. Methods: A retrospective cross-sectional study was conducted at the Manipal College of Medical Sciences, Pokhara, including 156 patients who underwent LC from January 2024 to June 2025. Demographic, clinical, laboratory, and ultrasonographic data were analyzed, with p-value<0.05 is considered significant. Results: Among 156 patients, 109(69.9%) were female and 47(30.1%) males. Difficult LC was significantly associated with age ≥50 years, BMI ≥30 kg/m², multiple attacks, WBC >11,000/mm³, GB wall >3 mm, pericholecystic collection, and stone size >25 mm (p-value<0.05). Conversion to open surgery was significantly related to BMI ≥30, multiple attacks, GB wall >3 mm, pericholecystic collection, stone size >25 mm, and multiple stones (p-value<0.05). Conclusion: Older age, obesity, recurrent attacks, raised WBC count, thickened gallbladder wall, pericholecystic collection, and larger or multiple stones were significant predictors of difficult LC and conversion. Recognizing these factors preoperatively aids in surgical planning and patient counselling, minimizing complications and conversion rates.